Effects of Health Literacy, Self-Efficacy, and Depression on Self Care Adherence in Patients with Ischemic Stroke - Min-Jin Jo; Eun-Mi Kim (Journal of Fundamental Nursing Science, 2026)
Purpose: This study aimed to assess health literacy, self-efficacy, depression, and self-care adherence among patients with ischemic stroke and to identify factors associated with self-care adherence. Methods: This crosssectional survey included 192 patients with ischemic stroke who were receiving outpatient care after hospitalization at P University Hospital in B City. Data were collected from April 22 to September 3, 2024, using structured questionnaires. The data were analyzed using SPSS/WIN 28.0 with descriptive statistics, the independent t-test, one-way analysis of variance, Pearson's correlation coefficient, and multiple linear regression. Results: The mean scores were 61.46±8.48 for health literacy, 95.65±10.17 for self-efficacy, 12.40±9.35 for depression, and 87.81±10.03 for self-care adherence. Self-care adherence differed significantly according to age (F=9.56, p